The readiness of pre-service integrated science teachers toward the next generation science standards - Parmin Parmin; Miranita Khusniati (LPMPP Universitas Negeri Yogyakarta, 2021)
This research examined the readiness of pre-service integrated science teachers in Indonesia in following the dimensions of the next generation science standards. It employed a survey method combined with an examination of the readiness of pre-service integrated science teachers who are currently studying in five colleges in Indonesia. The survey collected the data from 218 respondents, consisting of managers of science education study programs, pre-service science teachers, science education lecturers, science teachers, school principals, and education practitioners. There were 131 pre-service science teachers participating in this study in addition to 40 science teachers with have more than seven years of service as a comparison. The survey instrument was designed and presented in the form of docs.google.com, consisting of 12 questions. Learning evaluation experts validated the instrument before it was administered to the respondents. This study found that pre-service science teachers were not prepared due to three aspects: mastery of concepts; digital literacy and teaching how to apply scientific concepts in life. The achievement of future science teacher criteria for pre-service teachers is higher than teachers, except for aspects of teaching skills and human literacy.